2001
DOI: 10.1051/0004-6361:20011115
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent coupling of radiative transfer and dynamics in dust-driven winds

Abstract: Abstract. Models of stationary dust-driven winds of late-type stars are investigated. The flow is described successively using three models which couple, in spherical symmetry, the grain-gas dynamics in a self-consistent way with radiative transfer. Complete radiative transfer including multiple scattering, absorption and thermal emission is taken into account to determine the temperature of dust grains which in turn governs their thermal emission. The medium is not necessarily optically thin. The first model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…After decades of theoretical and observational studies, the mechanisms in which the wind acceleration occurs are still poorly understood. Due to the stellar high luminosity and low effective temperature, several authors have proposed radiativelly dust‐driven models to explain the observed wind properties (Elitzur & Ivezic 2001; Liberatore, Lafon & Berruyer 2001; Woitke & Niccolini 2005). At the pulsating phase, acoustic waves generate high‐density shells that could allow dust to form near the stellar surface.…”
Section: Introductionmentioning
confidence: 99%
“…After decades of theoretical and observational studies, the mechanisms in which the wind acceleration occurs are still poorly understood. Due to the stellar high luminosity and low effective temperature, several authors have proposed radiativelly dust‐driven models to explain the observed wind properties (Elitzur & Ivezic 2001; Liberatore, Lafon & Berruyer 2001; Woitke & Niccolini 2005). At the pulsating phase, acoustic waves generate high‐density shells that could allow dust to form near the stellar surface.…”
Section: Introductionmentioning
confidence: 99%
“…So far this phenomenon has almost exclusively been studied in stationary winds (e.g. Krüger et al 1994, henceforth KGS94;Krüger & Sedlmayr 1997;or Liberatore et al 2001) or non-pulsating stars (e.g. Simis et al 2001;or Sandin & Höfner 2003, henceforth Paper I).…”
Section: Introductionmentioning
confidence: 99%
“…We have added the diffusive collisions term to the first two approximations. Berruyer & Frisch derived the following approximation of C D,common (see also, Liberatore et al 2001;Mastrodemos et al 1996),…”
Section: Numerical Issues In the Rhd3-systemmentioning
confidence: 99%
“…However, without detailed modeling it is not clear quantitatively how large the effect due to the coupling will be. The most recent works concerning the influence of the treatment of the gas and dust phases have been carried out by Liberatore et al (2001), SID01 and Steffen et al (1998). An overview of the handling of the gas-dust interaction in earlier AGB wind models is presented by SID01.…”
Section: Introductionmentioning
confidence: 99%